COMPARISON OF EFFICACY OF TOPICAL ADAPALENE PLUS ORAL AZITHROMYCIN AND TOPICAL ADAPALENE PLUS ORAL DOXYCYCLINE IN TREATMENT OF ACNE VULGARIS - Ullah, Ghafoor; Farhad Ali; Mohammad Majid Paracha; Sahibzada Mehmood Noor; Jawad Naeem (Journal of Ayub Medical College Abbottabad, 2022)
Background: Acne vulgaris is a commonly diagnosed dermatological condition characterised by pilosebaceous unit blockage or inflammation. It may manifest as inflammatory, non-inflammatory, or a combination of the two. The acne vulgaris mostly the face of indvivdual and chest and back of individual is also affected sometime. the aim of my research is to compare the effectiveness of topical adapalene plus oral azithromycin versus topical adapalene plus oral doxycycline in treating acne. Acne is one of most common reason compelling a patient to see dermatological advice. Our goal is to find the most effective antibiotic to produce the best outcomes with the fewest possible unwanted effect (side effects) and a maximum level of patient satisfaction. Methods: From May 1 to October 31, 2019, a randomised control trial was performed at Dermatology department MTI Lady Reading Hospital Peshawar. Using the lottery form, all of the patients were split into 2 groups. For 12 weeks, patients in Group A were given oral doxycycline 100 mg once daily and topical adapalene, while patients in Group B were given oral azithromycin 250 mg on alternating days and topical adapalene. All patientswere followed at the end of 12 weeks after start of therapy to determine the efficacy in term of clearance of at least 60% of the number of lesions from baseline. Results: In Group A, 22 (59.45%) patients expressed positive results whereas in Group B, only 9 (24.32%) patients expressed positive results. p-value (0.0021.) Conlcusion: My data suggest that oral doxycycline 100mg in combination with adapalene gave better results as compared to oral azithromycin which was also found well-tolerated option for treatment of acne on face.